HUKUM ISLAM DALAM PANDANGAN PEMIKIR MUSLIM KONTEMPORER DAN ORIENTALIS - Muhammad Hizbullah; Haidir Haidir (TAQNIN: Jurnal Syariah dan Hukum, 2022)
Islamic law which in English is called Islamic Law. The main sources of Islamic law are the Qur'an and al-Sunnah. While the additional sources of law are ijma' and qiyas. With this source of Islamic law, it becomes the basis for answering and solving problems of Islamic law both in the early Islamic era as well as contemporary Islamic law problems. Islamic law itself is believed to be for Muslims as a law that is sourced from God's revelation. This is based on the sources of Islamic law derived from the Koran and the Sunnah. However, it is recognized that the Qur'an and al-Sunnah do not always appear explicitly for every problem of life, while the problems faced are increasingly numerous and complex. Therefore, the role of reason and revelation in the determination of Islamic law is very much needed.The purpose of this study was to find out how contemporary and western Muslim thinkers view Islamic law which is considered very elastic in the dynamics of social change. Which grows from various situations and conditions surrounding mankind. This ontological reality of Islamic law then gave birth to an epistemology of fiqh which is basically the resultant and interaction of the scholars with the social facts that surround it.